(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Poor implementation of quality assurance programs in the radiation industry has been a major setback in our locality. Several studies revealed that occupational workers are exposed to many potential hazards of ionizing radiation during radio-diagnostic procedures, yet radiation workers are often not monitored. This study aims to evaluate the occupational exposure of the radiation workers in Federal Medical Centre Katsina, and to compare the exposure with recommended occupational radiation dose limits. The quarterly readings of 20 thermo-luminescent dosimeters (TLDs’) used by the radiation workers from January to December, 2019 were collected from the facility’s radiation monitoring archive, and subsequently assessed and analyzed. The results indicate that the average annual equivalent dose per occupational worker range from 0.74 to 1.20 mSv and 1.28 to 2.21 mSv for skin surface and deep skin dose, measured at 10 mm and 0.07 mm tissue depth respectively. The occupational dose was within the recommended national and international limits of 5 mSv per annum or an average of 20 mSv in 5 years. Therefore, there was no significant radiation exposure to all the occupational workers in the study area. Though, the occupational radiation dose is within recommended limit, this does not eliminate stochastic effect of radiation. The study recommended that the occupational workers should adhere and strictly comply with the principles of radiation protection which includes distance, short exposure time, shielding and proper monitoring of dose limits. Furthermore, continuous training of the radiation workers is advised.